The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0225560
|View full text |Cite
|
Sign up to set email alerts
|

Oral feeding with probiotic Lactobacillus rhamnosus attenuates cigarette smoke-induced COPD in C57Bl/6 mice: Relevance to inflammatory markers in human bronchial epithelial cells

Abstract: COPD is a prevalent lung disease with significant impacts on public health. Affected airways exhibit pulmonary neutrophilia and consequent secretion of pro-inflammatory cytokines and proteases, which result in lung emphysema. Probiotics act as nonspecific modulators of the innate immune system that improve several inflammatory responses. To investigate the effect of Lactobacillus rhamnosus (Lr) on cigarette smoke (CS)-induced COPD C57Bl/6 mice were treated with Lr during the week before COPD induction and thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…In this scenario, it is important to draw our attention to the fact that even in mice from the Basal group, IL-10 levels vary a lot, and thus it is possible to find values of IL-10 a little bit higher than those found in most studies. In fact, diverse authors have also found values higher than 50 pg/ml in BALF of mice from the Basal group (33)(34)(35)(36). Our results are in accordance with findings in which IL-10 level in BALF of the Basal group reached 1,500 pg/ml (37).…”
Section: Discussionsupporting
confidence: 92%
“…In this scenario, it is important to draw our attention to the fact that even in mice from the Basal group, IL-10 levels vary a lot, and thus it is possible to find values of IL-10 a little bit higher than those found in most studies. In fact, diverse authors have also found values higher than 50 pg/ml in BALF of mice from the Basal group (33)(34)(35)(36). Our results are in accordance with findings in which IL-10 level in BALF of the Basal group reached 1,500 pg/ml (37).…”
Section: Discussionsupporting
confidence: 92%
“…In vitro experiment has demonstrated that L. rhamnosus NutRes1 can reduce inflammatory mediators produced by cigarette-activated human macrophages ( 124 ). Moreover, oral feeding of L. rhamnosus (strain not shown) increases levels of IL-10 as well as SOCS3 and TIMP1/2, and attenuates lung injury of COPD induced by cigarette in C57BL/6 mice ( 21 ). Additionally, the development of COPD is associated with reduction of Lactobacillus spp.…”
Section: Beneficial Role Of Lactobacillus In Respi...mentioning
confidence: 99%
“…Meanwhile, emerging evidence shows that Lactobacillus can also modulate respiratory immunity ( 13 16 ). Administration of Lactobacillus confer a beneficial role in respiratory diseases including respiratory tract infections (RTIs), asthma, lung cancer, cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD) ( 17 21 ). Administration of Lactobacillus may be an alternative strategy to alleviate respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In the COPD group, which was orally administered L. rhamnosus three times per week, the influx of inflammatory cells into the airways was inhibited compared to that in the COPD group that did not receive L. rhamnosus. It was involved with various immune responses [44].…”
Section: Properties As a Probiotic Against Various Diseasesmentioning
confidence: 99%